EMPLOYMENT LAW POLICY AND PROTECTION OF INDONESIAN MIGRANT WORKERS - Ade Risna Sari; Sulaiman; Haris Mirza Saputra (INJOSEDU: International Journal of Social and Education, 2025)
One group that is susceptible to abuse and human rights breaches is migrant laborers. The purpose of this review of the literature is to look at Indonesia's migrant worker protection laws and policies. Drawing from the literature analysis, it is evident that while regulations exist to safeguard migrant workers, inadequate oversight and enforcement are impeding their effective implementation. For migrant worker protection to be effective, regulation, implementation, and monitoring must function together. The study's findings also emphasize how crucial it is for key government agencies, non-governmental organizations, and other stakeholders to work together to implement comprehensive policies for the protection of migrant workers. The issues of protecting migrant workers, like stopping unlawful recruitment techniques and safeguarding migrant workers in emergency situations, require effective collaboration. There is an opportunity for Indonesia to strengthen a more progressive legal framework to protect the basic rights of migrant workers. With a better understanding of labor law policies and the protection of migrant workers, Indonesia has the opportunity to improve the conditions and rights of migrant workers in the future. Concrete measures, such as increased supervision of recruitment agencies, providing access to justice for migrant workers, and improving the protection of the basic rights of migrant workers are needed to improve the effectiveness and sustainability of migrant worker protection in Indonesia.